DEVELOPMENT AND VALIDATION OF STABILITY INDICATING RP-HPLC METHOD FOR NATAMYCIN IN BULK AND OPHTHALMIC DOSAGE FORMS. - Chaudhari, Jigar; Chhabra, G. S. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: This study was aimed to develop stability indicating RP-HPLC method for analysis of Natamycin and its dosage form according to theICH Q1A (R2) guidelines. Methods: Successful separation of drug from degradation products formed under stress conditions was achieved by a gradient HPLC method,performed onSeries 200 UV–visible detector by using Kromasil C18(100 x 4.6 mm, 5 µm) column; the flow rate was 1 ml/min, injected volume 20μL, the optimised mobile phases consist of Solvent A (Methanol) and Solvent B (Phosphate Buffer pH 3.5, adjusted pH with o-phosphoric acid) and UV detection was carried out at 304 nm. Results: The retention time of Natamycin was 8.96±0.10 minutes.The method was validated with respect to system suitability, linearity, precision, accuracy, limit of detection (LOD), limit of quantification (LOQ) and robustness. Linearity (20–100 μg/ml), LOD and LOQ was found to be 1.2 and 3.66 μg/ml respectively.The RSD for intra-day (0.59-0.86) and inter-day (0.44-0.96) precision were found to be less than 1 %. The mean percentage recovery was 100±2% which shows good agreement with the labelled amount in the ophthalmic formulations.Natamycin was exposed to acid-base hydrolytic, oxidative, thermal and photolytic stress conditions. The forced degradation studies were performed by using 0.01 N HCl (8.62%), 0.01 N NaOH (9.18 %), 15 % H2O2(24.13 %), thermal (100 °C, 5.13%) and sunlight (29.41%). Conclusion: Natamycin issusceptible towards acidic, basic, oxidative and photolytic conditions in comparison to unaffected by thermal degradations.The method is simple, specific, precise, robust and accurate for the determination of Natamycin in ophthalmic formulations. Keywords: Natamycin, RP-HPLC, Stability Indicating Method, Validation, Forced degradation.